2009
DOI: 10.1021/mp800136v
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cationic Lipid That Delivers siRNA and Enhances Therapeutic Effect in Lung Cancer Cells

Abstract: We have developed lipid-polycation-DNA (LPD) nanoparticles containing DOTAP and targeted with polyethylene glycol (PEG) tethered with anisamide (AA) to specifically deliver siRNA to H460 human lung carcinoma cells which express the sigma receptor. A novel non-glycerol based cationic lipid which contains both a guanidinium and a lysine residue as the cationic headgroup, i.e. DSGLA, downregulated pERK more efficiently in H460 cells than DOTAP. As demonstrated by using fluorescently labeled siRNA, LPD-PEG-AA prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 52 publications
0
76
0
Order By: Relevance
“…Major problems of siRNA delivery include poor cellular uptake, low stability, and rapid clearance from the systemic circulation. We have developed a cationic lipid containing both a guanidinium and a lysine residue as a cationic head group that can down-regulate mitogenactivated protein kinase (MAPK) signaling, form cationic liposome-polycation-DNA (LPD) to intravenously deliver siRNA to the solid tumor in high efficiency, and achieve a synergistic therapeutic effect with siRNA on a human lung cancer model (6). In this study, we further explored the biological activity of the guanidinium-containing cationic lipid, i.e.…”
mentioning
confidence: 99%
“…Major problems of siRNA delivery include poor cellular uptake, low stability, and rapid clearance from the systemic circulation. We have developed a cationic lipid containing both a guanidinium and a lysine residue as a cationic head group that can down-regulate mitogenactivated protein kinase (MAPK) signaling, form cationic liposome-polycation-DNA (LPD) to intravenously deliver siRNA to the solid tumor in high efficiency, and achieve a synergistic therapeutic effect with siRNA on a human lung cancer model (6). In this study, we further explored the biological activity of the guanidinium-containing cationic lipid, i.e.…”
mentioning
confidence: 99%
“…Banerief et al [77] first demonstrated the use of the selective sigma ligand namely anisamide to mediate efficient targeting of liposomal drugs to sigma receptor-expressing prostate cancer cells in vitro and in vivo. Since then there have been several articles reporting the application of anisamide targeting nanoparticles for the cell specific delivery of therapeutic siRNA [78][79][80] .…”
Section: Serum Stabilitymentioning
confidence: 99%
“…As these ABCD formulations are nearly neutral or even negative in charge, the remarkable gene silencing data when administered systemically must be a result of active cell-specific targeting. Li and colleagues developed a nanoparticle formulation for successfully systemic delivery of siRNA into xenograft [122,80] and metastatic tumours [78,79] which produced anti-cancer effects. In this system, the nucleic acids (siRNAs and carrier DNA), a polycationic peptide (protamine) and a cationic liposome, were initially prepared in a condensed core.…”
Section: "Abcd" System -Based Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…They found LPD vectors to be more efficient and less cytotoxic compared to conventional cationic liposomal vectors. Later, they modified LPDs through different cationic liposomes wherein LPDs were used to deliver antisense oligodeoxynucleotide and siRNA (Li & Huang, 2006;Chen et al, 2009;Gao & Huang, 2009). As a cationic polymer, PEI is commonly used for the delivery of genes.…”
Section: Hybrids Of Cationic Liposomes and Polymersmentioning
confidence: 99%